Advantage of Increasing Movement Speed in Young Volleyball Players Based on Exercises with Determined Pulsometric Value - Odilova Feruza Valizhon's (International Journal on Integrated Education, 2022)
On the basis of the analysis of the results of the study, justification of the priority and necessity of the development of the velocity of volleyball players through exercises, the effectiveness of which should be determined by their pulse rate. It is noted that such exercises can prevent premature fatigue and preserve the quality of game actions.